(untitled) (Sociología y tecnociencia, 2021)
This study aims to explore how the political dynamics in the local election of Makassar City in 2018. In particular, this study reconnoitered the causes of the victory of empty box and analyze the role of political parties and incumbents in the candidacy process and election. Qualitative research methods were used in this research. Documentation was carried out to obtain data related to actor networks in the local election, vote acquisition, election regulations and as well as political party support in the local election, which is obtained from books, journals and news in the mass media. In addition, FGD was carried out from stakeholders inviting academics, students and NGO activists to obtain data and interpretations of the collected data. Qualitative descriptive analysis was carried out by interpreting the collected data, verifying and generalizing the data to conclude this research. This research revealed that the empty box in the local election of Makassar City is actually not an empty box, nonetheless it is the representation of the incumbent who was disqualified from the local elections. Most of the political parties supported the sole candidate formally. It was found that there was a difference between party policy at the local level and party policies at the national level. Further, the party decision making was found to be centralized.